Sztuka młodych jako przestrzeń dialogu wewnętrznego. Refleksje na temat pewnej tendencji w trzech krótkich wspomnieniach - Pokrywka, Przemysław (Wydział Sztuki UR, 2018)
The Solvay Cracow Center for Contemporary Art is a culture institution promoting young artists. In the past decade it has exhibited a few dozen projects by students and graduates of art academies. The wide range of interests and characters has created a colorful mosaic of artistic stances. It is against this background that the author of this article presents three artists, who, due to their intellect and talent, are intriguing art personalities. They are not anonymous in the younger generation of Polish art, however they seem to be staying on its sidelines. The author presents Michał Marek, an artist connected with Wrocław, who has exhibited a collection of incomplete, crisscrossed paintings – evidence of a crisis an artist faces on his way. The article also presents Arkadiusz Andrejkow, who in the fall of 2012 showed in the Centre a painting exhibition titled “Family matters”, inspired by photographs found in an old wardrobe. Faced with images of his nearest and dearest, cultivating the memory of his relatives, Andrejkow provokes the viewer into a deeper reflection on the problem of transition and one’s own identity, often difficult in a historical context. The third artist is Kamil Kuzko, who consciously rejects current trends and fashions. In his works one can see a whole range of solutions reminiscent of Orthodox icons and frescoes. Of special interest is his schematic presentation of male faces, many of tchem being the artist’s self-portraits, whose form is modeled on the art of Eastern Church.
The art of the young as a space of inner dialogue. Reflections on a certain tendency in three short recollections
Keywords: Michał Marek; Arkadiusz Andrejkow; Kamil Kuzko; malarstwo; dialog; wystawa; młoda sztuka; painting; dialogue; exhibition; young art